Selective Histone Deacetylase 6 Inhibitors Restore Cone Photoreceptor Vision or Outer Segment Morphology in Zebrafish and Mouse Models of Retinal Blindness - Sundaramurthi, Husvinee; Roche, Sarah L.; Grice, Guinevere L.; Moran, Ailis; Dillion, Eugene T.; Campiani, Giuseppe; Nathan, James A.; Kennedy, Breandán N. (Frontiers in Cell and Developmental Biology, 2020)
Blindness arising from retinal or macular degeneration results in significant social, health and economic burden. While approved treatments exist for neovascular (‘wet’) age-related macular degeneration, new therapeutic targets/interventions are needed for the more prevalent atrophic (‘dry’) form of age-related macular degeneration. Similarly, in inherited retinal diseases, most patients have no access to an effective treatment. Although macular and retinal degenerations are genetically and clinically distinct, common pathological hallmarks can include photoreceptor degeneration, retinal pigment epithelium atrophy, oxidative stress, hypoxia and defective autophagy. Here, we evaluated the potential of selective histone deacetylase 6 inhibitors to preserve retinal morphology or restore vision in zebrafish atp6v0e1-/- and mouse rd10 models. Histone deacetylase 6 inhibitor, tubastatin A-treated atp6v0e1-/- zebrafish show marked improvement in photoreceptor outer segment area (44.7%, p = 0.027) and significant improvement in vision (8-fold, p = <0.0001). Tubastatin A-treated rd10/rd10 retinal explants show a significantly (p = 0.016) increased number of outer-segment labelled cone photoreceptors. In vitro, ATP6V0E1 regulated HIF-1α activity, but significant regulation of HIF-1α by histone deacetylase 6 inhibition in the retina was not detected. Proteomic profiling identified ubiquitin-proteasome, phototransduction, metabolism and phagosome as pathways, whose altered expression correlated with histone deacetylase 6 inhibitor mediated restoration of vision.